Pemilihan Warga Penerima Bantuan Program Keluarga Harapan (PKH) Menggunakan Metode Simple Additive Weighting (SAW) dan User Acceptance Testing (UAT) - Pujianto, Pujianto; Mujito, Mujito; Prabowo, Danang; Prasetyo, Basuki Hari (Jurnal Informatika Universitas Pamulang, 2020)
PKH (Hope Family Program) is a government assistance program to help people experiencing poverty problems this program is an aid from the ministry of social affairs in order to reduce social inequality among poor groups. so it is hoped that in the long run it can break the relationship of poverty between generations. so that the next generation can come out of the abyss of poverty due to the increasing quality of human resources produced. The aspects used are health aspects, educational aspects and aspects of social welfare.Â  The selection of citizens who are not objective recipients of the PKH Program makes it a problem. Many protested against the village's devices in determining which residents were entitled to assistance and sometimes acts of vandalism. so that in this study want to help village devices in selecting citizens who are entitled to receive assistance using the system. The methods used are Simple Additive Weighting (SAW), and User Acceptance Testing (UAT) is used to test the feasibility of the application. A sample of 10 residents who were recommended to receive PKH assistance obtained the results that Mr. Anwar who ranked first for assistance with a score of 80.5 And for the testing UAT earned an average value of 87%.